PERAN AGEN ASURANSI SYARIAH DALAM MENINGKATKAN PEMAHAMAN MASYARAKAT TENTANG ASURANSI SYARIAH - Edi Hariyadi; Abdi Triyanto (JURNAL EKONOMI DAN PERBANKAN SYARIAH, 2017)
ABSTRAK. Permasalahan yang akan diangkat dalam penelitian ini adalahbagaimana peran seorang agen asuransi dalam meningkatkan pemahaman terhadapa asuransi takaful. Dalam penelitian ini juga berusaha menjawab bagaimana sikap perilaku nasabah terhadap eksistensi asuaransi syariah. Kedua bagaimana kerja keras seorang agen asuransi syariah dalam meningkatkan kesadaran masyarakat. Model penelitian ini adalah penelitian kepustakaan. Hasil daripada penelitian ini, agen memiliki peran dalam mengakses informasi, menjaga image asuransi syariah, memberikan solusi dan konsultasi terhadapnasabah yang prospektif. Dengan begitu, pemahamanan masyarakat akan manfaat takaful akan menjadi lebih baik.Keywords: Agent Asuransi Syariah, Peran Agen asuransi syariah,pemahaman masyarakatABSTRACT. The subject matter to be discussed in this paper is how the role of an Islamic insurance agent in increasing public understanding of Takaful. In addition this paper will try to answer: how people's attitude toward the existence of Islamic insurance; and how should the efforts of an Islamic insurance agent to increase insurance awareness for the community. This paper focuses the discussion of an agent as an intermediary between the Takaful Islamic insurance company with the community. The method used in this paper is to study literature (Library Research), namely by rethinking simultaneously collects some writing and previous research results related to the presence and role of thefunction of an agent. This results in writing that there are a few roles Takaful agent, such as access to information, guard the good image of Islamic insurance companies, power marketers Islamic insurance products, providing solutions and services to prospective customers as well as provide insight to the public right of Takaful. On the basis of the understanding of Takaful then the public will know and understand the importance of using Takaful.Keywords: Islamic Insurance Agent, Role of Agent, Understanding of society